Inhibition of nitrogen mineralization in young humic fractions by anaerobic decomposition of rice crop residues - Olk, D.C.; Samson, M.I.; Gapas, P. (Wiley, 2007)
Field observations indicate a long‐term decrease in crop uptake of N derived from soil organic matter under continuous production of irrigated lowland rice (Oryza sativa L.). Decreased availability has been associated with an accumulation of phenolic lignin residues in soil organic matter, which can chemically bind N. To evaluate the hypothesis that the decrease in N availability results primarily from anaerobic decomposition of incorporated crop residues, 15N‐labelled fertilizer was applied three times during one growing season in a field study that compared anaerobic decomposition with aerobic decomposition for annual rotations of rice (Oryza sativa L.)–rice and rice–maize (Zea mays L.). Contents of 15N and total N during the growing season were measured in humic fractions and total soil organic matter. Results indicated an inhibition of N mineralization for the rice–rice rotation with anaerobic decomposition of crop residues, both for 15N that was immobilized after application and for total N. The inhibition was strongest for 15N that was applied at planting. It became more evident as the season progressed and reached significant levels during mid‐season stages of plant growth when crop demand for N peaks. These results were clearest for a young, phenolic‐rich humic fraction that was active in 15N immobilization and remineralization. Comparable but less significant trends were evident for a more recalcitrant humic fraction and for soil organic matter. Trends in crop‐N uptake associated the combination of rice–rice rotation and anaerobic decomposition with inhibited uptake of soil organic N but uninhibited uptake of fertilizer N. Increased aeration of rice soils through aerobic decomposition of crop residues or crop rotation is a promising management technique for improving soil N supply in lowland rice cropping.